2017
DOI: 10.5114/aoms.2015.55147
|View full text |Cite
|
Sign up to set email alerts
|

Altered sympathovagal balance and pain hypersensitivity in TNBS-induced colitis

Abstract: IntroductionPain hypersensitivity, abnormal motility and autonomic dysfunction contribute to functional symptoms of inflammatory bowel disease (IBD).Material and methodsThe aim of this study was to assess: nociceptive thresholds for mechanical allodynia (MA) and thermal hyperalgesia (TH), intestinal motility (distal colonic transit and emptying), and cardiac autonomic neuropathy (indices of heart rate variability – HRV) in male Wistar rats with experimental trinitrobenzene sulfonic acid (TNBS) induced colitis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
(32 reference statements)
1
15
0
Order By: Relevance
“…It is similar to the effect of EA on visceral hypersensitivity of IBS induced by acetic acid [36], colorectal distension neonatal rat [49], formaldehyde [50], and other injuries previously reported. Previous studies have shown that chemical inflammatory injury to the colon can cause peripheral and central sensitization and increased excitability in neurons [40] and that astrocytes play an important role in the occurrence and maintenance of sensitization [41]. Our findings that inhibition of astrocyte activity reduced visceral hypersensitivity of rats with IBS induced by acetic acid are consistent with the previously reported role of astrocytes in other types of inflammatory visceral hypersensitivity pathology [51].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is similar to the effect of EA on visceral hypersensitivity of IBS induced by acetic acid [36], colorectal distension neonatal rat [49], formaldehyde [50], and other injuries previously reported. Previous studies have shown that chemical inflammatory injury to the colon can cause peripheral and central sensitization and increased excitability in neurons [40] and that astrocytes play an important role in the occurrence and maintenance of sensitization [41]. Our findings that inhibition of astrocyte activity reduced visceral hypersensitivity of rats with IBS induced by acetic acid are consistent with the previously reported role of astrocytes in other types of inflammatory visceral hypersensitivity pathology [51].…”
Section: Discussionsupporting
confidence: 92%
“…Compared with Model group, EA at Zusanli (ST 36) and Shangjuxu (ST 37) (100 Hz for 1.05 s, 2 Hz for 2.85 s alternately, pulse width for 0.1 ms, 1 mA, 30 min/d, once a day) significantly reduced the behavioral AWR scores of IBS rats at 20 mmHg (P < 0.05, Figure 1 Figure 1(e)), suggesting that EA significantly inhibited chronic visceral hypersensitivity in rats with acetic acid-induced IBS model. Previous studies have shown that chemical inflammatory injury of the colon caused peripheral and central sensitization and neurons [40] show increased excitability and glial cells were involved in the occurrence and maintenance of sensitization [41]. In order to verify whether astrocytes in the spinal cord were also involved in spinal sensitization in visceral hypersensitivity in our model, we conducted intrathecal injection of fluorocitrate (FCA), an inhibitor of glial cell activity, to observe the effect of FCA on AWR score of the rat with visceral hypersensitivity.…”
Section: E Effect Of Fca and Electroacupuncture On Visceral Hypersensmentioning
confidence: 99%
“…Collectively, it is tempting to speculate that butyrate consumption stimulates GLP-1 secretion from L cells of the GI tract, which activates GLP-1 receptor signalling in the vagal nerve and consequently induces hypothalamic satiety signalling. In addition, another important function of the gut-brain neural circuit is to regulate the intestinal transit,34 which plays an important role in nutrient harvest, thereby directly influencing host energy metabolism. A previous study has shown that butyrate increases colonic motility 35.…”
Section: Discussionmentioning
confidence: 99%
“…The ANS via its parasympathetic branch is a central mediator of the microbiota-gut-brain axis, dysfunction of which is thought to underlie both functional and inflammatory GI disorders (Bonaz, Bazin, & Pellissier, 2018). GI inflammation has been linked to negative emotional states and autonomic reactivity in both animal models and human studies (Bonaz et al, 2016;Cielsielczyk, Furgała, Dobrek, Jusczak, & Thor, 2017;Ghia et al, 2009). Vagally mediated anti-inflammatory action is demonstrated in animal models of inflammatory bowel disease and depressive-like behaviors are linked to increased inflammation via vagal nerve pathways (Ghia, Blennerhassett, & Collins, 2008;Ghia et al, 2009;Ghia, Blennerhassett, Kumar-Ondiveeran, Verdu, & Collins, 2006).…”
Section: Emerg Ing E Viden Ce For De Velopmental Pathwaysmentioning
confidence: 99%